2019
DOI: 10.34218/ijaret.10.6.2019.015
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Characteristics of Fly Ash Reinforced Aluminium Metal Matrix Composite-Art of Review   

Abstract: Composites are widely utilized in the industries like automobile, aircraft, space craft, transport, generation of wind-power and so on due to its lightweight and inexpensive. Recently, dissimilar physical and chemical features of materials are intercorporate to produce an innovative composite material. Many researches had performed research on those composite materials. In this research, fly ash materials are utilized in the form of reinforcement due to their improved mechanical characteristics like enhanced U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…All of these values were obtained by doing the different mechanical tests for AHMMC.This is also evident in the study conducted by (Coyal et al 2020).where the values are increasing with weight fraction and stirring time likewise exhibited in (Palanichamy et al 2019). (p < 0.001 one-way ANOVA) and this statement is in agreement with the findings of (Kumar et al 2012).For B4C fly ash reinforced AA6061, (Bauri and Yadav 2017).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…All of these values were obtained by doing the different mechanical tests for AHMMC.This is also evident in the study conducted by (Coyal et al 2020).where the values are increasing with weight fraction and stirring time likewise exhibited in (Palanichamy et al 2019). (p < 0.001 one-way ANOVA) and this statement is in agreement with the findings of (Kumar et al 2012).For B4C fly ash reinforced AA6061, (Bauri and Yadav 2017).…”
Section: Discussionsupporting
confidence: 57%
“…Around 612 research articles were reported on experimental Investigation on tensile strength, compressive strength, hardness and corrosion resistance of Al6061 (Coyal et al 2020) hybrid composite reinforced with 15% weight fraction of B4C+Fly ash and comparing the outputs with as-cast Al6061(Sendhil )the aluminum 6061 as a metal matrix composite material adding with B4c and flyash based on the weight fraction of 15% and(Bauri and Yadav 2017) comparing the outputs. (Palanichamy et al 2019). Investigation of mechanical properties adding fly ash reinforced aluminum metal matrix composite and review (Coyal et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, incorporation of boron carbide with Al7075 enhances the specific strength, specific stiffness, mechanical properties, and wear resistance of the composite [23,31]. These exceptional properties made boron carbide a good choice as a primary reinforcement for advanced applications in automotive, armaments, aircraft, and aerospace applications, especially for those parts which are subjected to very high temperatures and require high abrasion resistance [32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%